Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$F:\mathbb{R}^2 \to \mathbb{R}^2,\\ f(x,y)= ((x^3)-x),y)$

How can I check if this is surjective or not?

share|cite|improve this question
    
Have you looked up the definition of surjective? – gebruiker May 4 '14 at 14:02
    
Try to balance the parentheses. – Marc van Leeuwen May 4 '14 at 17:32
up vote 3 down vote accepted

This is surjective since $\forall\alpha\in\Bbb R:x^3-x=\alpha$ has at least one real root.

share|cite|improve this answer

$y$ has no influence to $x^3-x$ and we can choose $y$ any number.

It is enough to show that $r(x)=x^3-x$ is surjective. You can show it in many ways;

$lim_{x\to \infty}r(x)= \infty$ and $lim_{x\to -\infty}=-\infty$ and $r(x)$ continious so for any $a\in \mathbb R$ there exist $x$ such that $x^3-x=a$

share|cite|improve this answer

You can actually solve $x^3 + x = a$ for $x$.

Write it as $$x ^3 = a - x \tag1$$

Note that $(u-v)^3 = u^3 - 3u^2v + 3uv^2 - v^3$ can be rewritten as $(u-v)^3 = (u^3 - v^3) - 3uv(u - v)$

Now let $x = u - v$. You get $$x^3 = (u^3 - v^3) - 3uvx \tag2$$

Comparing (1) and (2), we see that we need to solve $u^3 - v^3 = a$ and $3uv = 1$.

From $3uv = 1$, we get $v = \dfrac{1}{3u}$. So

\begin{align} u^3 - v^3 &= a\\ u^3 - \dfrac{1}{27u^3} &= a\\ 27u^6 - 1 &= 27au^3 \\ 27u^6 - 27au^3 - 1 &= 0 \\ 27(u^3)^2 - 27a(u^3) - 1 &= 0 \\ u^3 &= \dfrac{27a \pm \sqrt{729a^2+108}}{54} & \{\text{Note that $729a^2 + 108 > 0$ for all $a$}\} \\ u^3 &= \dfrac{9a \pm \sqrt{81a^2+12}}{18} \\ u &= \left( {\dfrac{9a \pm \sqrt{81a^2+12}}{18}} \right)^{1/3}\\ \end{align}

If we let $u = \left( {\dfrac{9a + \sqrt{81a^2+12}}{18}} \right)^{1/3}$, then

\begin{align} u^3 - v^3 &= a\\ v^3 &= u^3 - a \\ v^3 &= \dfrac{9a + \sqrt{81a^2+12}}{18} - a\\ v^3 &= \dfrac{-9a + \sqrt{81a^2+12}}{18} \\ v &= -\left(\dfrac{9a - \sqrt{81a^2+12}}{18} \right)^{1/3} \\ \end{align}

So, a solution is

$$x = \left( {\dfrac{9a + \sqrt{81a^2+12}}{18}} \right)^{1/3} + \left( \dfrac{9a - \sqrt{81a^2+12}}{18} \right)^{1/3} \tag3$$

To verify this solution

Let $x = u-v$, where

$u = \left( {\dfrac{9a + \sqrt{81a^2+12}}{18}} \right)^{1/3}$ and $v = -\left( {\dfrac{9a - \sqrt{81a^2+12}}{18}} \right)^{1/3}$

Note that \begin{align} uv &= -\left( {\dfrac{9a + \sqrt{81a^2+12}}{18}} \right)^{1/3} \left( {\dfrac{9a - \sqrt{81a^2+12}}{18}} \right)^{1/3} \\ &= -\left[ \left( {\dfrac{9a + \sqrt{81a^2+12}}{18}} \right) \left( {\dfrac{9a - \sqrt{81a^2+12}}{18}} \right) \right]^{1/3} \\ &= -\left( \dfrac{81a^2 - (81a^2+12)}{324} \right)^{1/3}\\ &= -\left(-\dfrac{12}{324} \right)^{1/3}\\ &= \dfrac 13 \end{align}

and $u^3 - v^3 = \left( {\dfrac{9a + \sqrt{81a^2+12}}{18}} \right) + \left( {\dfrac{9a - \sqrt{81a^2+12}}{18}} \right) = a$

So \begin{align} x^3 + x &= (u-v)^3 + (u-v)\\ &= (u^3 - 3u^2v + 3uv^2 - v^3) + (u-v)\\ &= (u^3 - v^3) -3uv(u-v) + (u-v) \\ &= a - (u-v) + (u-v) \\ &= a \end{align}

share|cite|improve this answer
    
That's the only complete solution among all the answers. +1 – Arghya Chakraborty Jun 16 at 14:43

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.